Isorhamnetin 3-O-robinobioside from Nitraria retusa leaves enhance antioxidant and antigenotoxic activity in human chronic myelogenous leukemia cell line K562 - Boubaker Jihed; Sghaier Mohammed; Skandrani Ines; Ghedira Kamel; Chekir-Ghedira Leila (BMC, 2012)
Abstract Background In this report, the isorhamnetin 3-o-robinobioside and its original extract, the ethyl acetate extract, from Nitraria retusa leaves, were evaluated for their ability to induce antioxidant and antigenotoxic effects in human chronic myelogenous leukemia cell line. Methods Nitraria retusa products properties were carried out by firstly evaluating their effects against lipid peroxidation induced by H2O2, using the thiobarbituric acid reactive substances species (TBARS) assay, and proceeding to the assay of cellular antioxidant activity, then doing the comet assay. Results The isorhamnetin 3-o-robinobioside showed a protective effect against lipid peroxidation induced by H2O2. The same natural compound and ethyl acetate extract inhibited oxidation induced by 2,2'-azobis (2-amidinopropane) dihydrochloride in human chronic myelogenous leukemia cells with respectively 50% inhibitory concentration values of 0.225 mg/ml and 0.31 mg/ml, reflecting a significant antioxidant potential. The same two products inhibited the genotoxicity induced by hydroxyl radicals in the same human cell line (by 77.77% at a concentration of 800 μg/ml and by 80.55% at a concentration of 1000 μg/ml respectively). Conclusions The isorhamnetin 3- o-robinobioside and its original extract, the ethyl acetate extract, from Nitraria retusa leaves, have a great antioxidant and antigenotoxic potential on human chronic myelogenous leukemia cell line K562.